2020
DOI: 10.1039/c9ra08657a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of controlled-size silver nanoparticles for the administration of methotrexate drug and its activity in colon and lung cancer cells

Abstract: A controlled synthesis of methotrexate (MTX) silver nanoparticles (AgNPs-MTX) using borohydride and citrate as reduction and reduction/capping agents, respectively, was performed in order to obtain AgNPs-MTX conjugates with a narrow size distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 35 publications
0
14
0
2
Order By: Relevance
“…It has a short plasma circulation time (3-17 h) and a high rate of cell efflux, requiring high therapeutic doses (15-20 mg/m 2 , twice a week). Some side effects that this drug can cause are hair loss, decrease in the number of blood cells, liver damage, lung damage, among others [73,78,79].…”
Section: Methotrexate Anticancer Drugmentioning
confidence: 99%
See 1 more Smart Citation
“…It has a short plasma circulation time (3-17 h) and a high rate of cell efflux, requiring high therapeutic doses (15-20 mg/m 2 , twice a week). Some side effects that this drug can cause are hair loss, decrease in the number of blood cells, liver damage, lung damage, among others [73,78,79].…”
Section: Methotrexate Anticancer Drugmentioning
confidence: 99%
“…In 2020, Rozalen et al [73] synthesized AgNPs (mean size of 11.13 ± 2.3 nm), which were then coupled to methotrexate (AgNPs-MTX). AgNPs-MTX was obtained through chemical synthesis using sodium borohydride and citrate as reducing agents, acting citrate as also capping agent.…”
Section: Methotrexate Anticancer Drugmentioning
confidence: 99%
“…Rozalen et al [ 159 ] synthesized AgNPs (size of 11.13 ± 2.3 nm), then it is coupled with methotrexate (AgNPs-MTX) and it shows anti-cancer activity, and the lower dose of AgNPs-MTX was needed compared to free methotrexate, as well as the authors reported that the anti-cancer activity was more noticeable in the colon cancer cell line (HTC-116) than in the lung cancer cell line (A-549). Thapa et al prepared the nanocomposite of AgNPs embedded in graphene oxide (GO) and coupled with methotrexate (MTX-GO/AgNPs).…”
Section: Various Metallic Nanocarriers In Drug Delivery Systemsmentioning
confidence: 99%
“…[25] , [97] , [98] , [99] , [100] , [101] , [102] , [103] , [104] , [105] , [106] , [107] , [108] , [109] , [110] , [111] , [112] , [113] , [114] , [115] , [143] , [144] , [145] , [146] , [147] , [148] , [149] , [150] , [151] , [152] , [153] , [154] , [155] , [156] , [157] , [158] , [159] , [160] , [161] , [162] , [163] , [164] , [165] , [166] , [167] , [168] , [169] , [170] , [171] , [172] …”
Section: Uncited Referencesunclassified